Chapter 3
Chapter 3
SLIDES FOR
CHAPTER 3
BOOLEAN ALGEBRA
(continued)
Distributive Laws
Given an expression in product-of-sums form, the
corresponding sum-of-products expression can be
obtained by multiplying out, using the two distributive laws:
X(Y + Z) = XY + XZ (3-1)
(X + Y)(X + Z) = X + YZ (3-2)
1
10/3/2014
Example (3-4), p. 63
©2010 Cengage Learning
2
10/3/2014
Section 3.2, p. 64
©2010 Cengage Learning
3
10/3/2014
Section 3.2, p. 65
©2010 Cengage Learning
4
10/3/2014
Section 3.2, p. 66
©2010 Cengage Learning
Example 1:
Example 2:
5
10/3/2014
Dual Form:
(X + Y)(X’ + Z)(Y + Z) = (X + Y)(X’ + Z) (3-21)
Consensus Theorem
Proof
6
10/3/2014
7
10/3/2014
8
10/3/2014
9
10/3/2014
10
10/3/2014
11
10/3/2014
If y = z, then x + y = x + z (3-33)
If y = z, then xy = xz (3-34)
12